The Effect of Low Carbohydrate Diets on Preventing and Treating Carcinogen-Induced Lung Cancer in Mice. (29th May 2020) - Elisia, Ingrid; Cho, Brandon; Hay, Mariah; Yeung, Michelle; Kowalski, Sara; Wong, Jennifer; Lam, Vivian; Krystal, Gerald
Abstract: Objectives: Since cancer cells typically rely more on glycolysis than normal cells, we hypothesized that lowering carbohydrate intake may reduce cancer risk. We aimed to investigate the efficacy of low-carbohydrate (CHO) diets in preventing and treating a tobacco-specific carcinogen-induced lung cancer in female A/J mice. Methods: We evaluated the role of different types of CHO (easily digestible vs resistant), protein (casein vs. soy) and fat (fish vs. coconut vs. a mixture of oils) in modulating 4-(N-methyl-N-nitrosamino)-1-(3- pyridyl)-1-butanone (NNK)-induced lung nodule formation in these mice. To assess the efficacy of these diets in preventing NNK-induced lung nodule formation, we put these mice in the different diets for 2 weeks, intraperitoneally-injected NNK once a week for two weeks to initiate lung nodule formation. After 5 months, the lung nodules in these mice were counted. Results: The lowering of easily digestible CHO significantly reduced constitutive blood glucose levels and lung nodule formation in the mice. Interestingly, diets low in easily digestible starch, high in fish oil (FO) and soy protein (15%Amylose/Soy/FO) were the most effective at preventing the formation of NNK-induced lung nodules. To determine if this 15%Amylose/Soy/FO is also effective at slowing tumor progression, we fed NNK-injected A/J mice a Western diet until tumors were established (5 months post NNK) and then either switched them to the 15%Amylose/Soy/FO or kept them on the Western diet for 5 additional months. The 15%Amylose/Soy/FO diet prevented the formation of additional lung tumor nodules and reduced the size of the tumors, although no significant difference was observed in tumor stage. The reduction in size of the lung tumors on the 15%Amylose/Soy/FO diet was not due to a lower tumor proliferation (Ki67 index) but an increase in apoptosis, as determined by TUNEL assays. Conclusions: We conclude that a diet change that lowers glucose intake, incorporates FO and soy protein may be effective not only in preventing lung cancer formation but also in slowing the growth of established lung tumors. Funding Sources: Lotte & John Hecht Memorial Foundation.